Monte Carlo simulations and analysis of transmitted gamma ray spectra through various tissue phantoms - Moradi, Farhad; Khandaker, Mayeen Uddin; Alrefae, Tareq; Ramazanian, H.; Bradley, David Andrew (Elsevier, 2019)
Studies of radiation interactions with tissue equivalent material find importance in efforts that seek to avoid unjustifiable dose to patients, also in ensuring quality control of for instance nuclear medicine imaging equipment. Use of the Monte Carlo (MC) simulation tool in such characterization processes allows for the avoidance of costly experiments involving transmitted X- and γ-ray spectrometry. Present work investigates MC simulations of γ-ray transmission through tissue equivalent solid phantoms. Use has been made of a range of radionuclide gamma ray sources, 99m Tc, 131 I, 137 Cs, 60 Co (offering photons in the energy range from a few keV up to low MeV), popularly applied in medicine and in some cases for gauging in industry, obtaining the transmission spectra following their interaction with various phantom materials and thicknesses. In validation of the model, the simulated values of mass attenuation coefficients (μ/ρ) for different phantom materials and thicknesses were found to be in good agreement with reference values (NIST, 2004) to within 1.1% for all material compositions. For all of the primary photon energies and medium thicknesses of interest herein, results show that multiple scattering peaks are generally located at energies lower than 100 keV, although for the larger phantom thicknesses it is more difficult to distinguish single, double and multiple scattering in the gamma spectra. Transmitted photon spectra investigated for water, soft tissue, breast, brain and lung tissue slab phantoms are demonstrated to be practically independent of the phantom material, while a significant difference is observed for the spectra transmitted through bone that was proved to be due to the density effect and not material composition. © 2019 Elsevier Ltd